THE ROLE OF ISLAMIC BOARDING SCHOOLS IN DEVELOPING SANTRIPRENEURSHIP: A CASE STUDY OF PESANTREN AL-ITTIFAQ BANDUNG - Haidir, Yumna Adzra; Harjawati, Tri (Jurnal Visipena, 2025)
This study aims to examine the role of Islamic boarding schools in shaping santripreneurs through agribusiness-based education at Al-Ittifaq Islamic Boarding School in Bandung. Islamic boarding schools, as Islamic educational institutions, not only play a role in spiritual guidance but also serve as agents of socio-economic change. The concept of santripreneurs integrates Islamic values with entrepreneurial skills, thereby producing religious, independent, and productive santri. This study uses a qualitative approach with a descriptive case study method. Data were collected in June 2025 through interviews, observations, and documentation of the pesantren leader (Kyai), two administrators who also serve as managers and business administrators of the pesantren, and three santri who are active in agribusiness activities. The results show that Al-Ittifaq Islamic Boarding School acts as a facilitator of business learning, a role model for entrepreneurship, and an educational ecosystem that allows students to learn both business theory and practice. Students are involved in the management of agriculture, animal husbandry, and product distribution, thereby forming an entrepreneurial character based on Islamic values. This research confirms that Islamic boarding schools have a strategic role in producing a generation of santripreneurs who are able to respond to the challenges of the times while maintaining their Islamic identity.